Status of and Factors Influencing the Stigma of Chinese Young and Middle-Aged Maintenance Hemodialysis Patients: A Preliminary Study - Zhang, Nina; Lai, Fengxia; Guo, Yong; Wang, Lan (Frontiers in Psychology, 2022)
Many young and middle-aged maintenance hemodialysis patients suffer a poor prognosis, experience a series of problems during long-term treatment and are thus prone to stigma. This study was designed to analyze stigma in young and middle-aged maintenance hemodialysis patients and explore its influencing factors. This study was conducted as a cross-sectional descriptive study with a convenience sampling method and included 97 patients from Shanghai Jiao Tong University Affiliated Sixth People’s Hospital between November 2020 and February 2021. The Social Impact Scale, a demographic questionnaire, and hemodialysis indicators were used in the investigation. Patient biochemical indexes from hemodialysis were compared. Young and middle-aged maintenance hemodialysis patients had a medium level of stigma. Patients who had low income, were younger, were male, had long-term hemodialysis and were unemployed had significantly higher stigma scores than other patients (P<0.05). Age, gender, occupational status, annual household income and the duration of hemodialysis were found to be the main factors related to stigma in young and middle-aged maintenance hemodialysis patients by multiple regression analysis. Perceptions of hemodialysis-related stigma were common in our sample. Patients who had low income, were younger, were male, had long-term hemodialysis and were employed had a higher level of stigma, which deserves attention from clinical medical workers. Replication studies are needed to confirm these findings.